GENERAL PRINCIPLES OF INTERNATIONAL LAW AS PEREMPTORY NORMS OF INTERNATIONAL LAW - Đorđević Aleksovski, Sanja M. (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
The paper analyzes the relationship between general principles of law and peremptory norms (ius cogens) in contemporary international law, starting from Article 38(1)(c) of the Statute of the International Court of Justice and Article 53 of the Vienna Convention on the Law of Treaties. Special attention is paid to the question of whether general principles of law, traditionally understood as a subsidiary source of law, can acquire the status of norms from which no deviation is permitted. First, the nature and function of general principles of law are examined, distinguishing between principles derived from domestic legal systems and those inherent in the international legal order itself. The paper then analyzes the concept, elements, and legal effects of peremptory norms, with particular reference to the work of the International Law Commission and relevant judicial practice. The central part of the paper is devoted to doctrinal debate on the possibility of converting general principles into ius cogens norms, juxtaposing arguments that emphasize differences in their genesis and function with views highlighting material criteria, such as normative intensity and universal acceptance. Based on the analysis of specific examples, the paper shows that some peremptory norms have multiple origins and may reflect values contained in general principles of law. On this basis, the concept of a transversal hierarchy is developed, according to which ius cogens represents a meta-normative quality that may be inherent in norms of different formal origins. It is concluded that, although general principles of law generally retain their subsidiary function, the possibility is not excluded that certain principles, under strict conditions, may evolve into norms of the highest hierarchical rank, thereby confirming the value-based transformation of the international legal order. The transformation of general principles into ius cogens norms exemplifies the development of a truly global and value-based legal order.